2020
DOI: 10.3390/microorganisms8060882
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intestinal Microbiota and Fecal Calprotectin in Non-Toxigenic and Toxigenic Clostridioides difficile Colonization and Infection

Abstract: In this study, we aimed to evaluate the composition of the intestinal microbiota and level of fecal calprotectin in Clostridioides difficile-colonized patients. We included 102 C. difficile non-colonized (group I), 93 C. difficile colonized subjects (group II), and 89 diarrhea patients with C. difficile (group III). Chao1 index for alpha diversity and principal coordinate analysis was performed for beta diversity using QIIME. The mean relative abundance in each group was compared at the phylum and genus levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…These gut microbiota changes in symptomatic patients were accompanied by significantly higher levels of fecal calprotectin, comparatively with asymptomatic patients and controls. These data suggest that association of microbiota and inflammatory markers could be used to differentiate C. difficile colonization (CDC) from CDI ( Han et al, 2020 ).…”
Section: Clostridioides Difficile Infection and Dysbiosis In...mentioning
confidence: 99%
“…These gut microbiota changes in symptomatic patients were accompanied by significantly higher levels of fecal calprotectin, comparatively with asymptomatic patients and controls. These data suggest that association of microbiota and inflammatory markers could be used to differentiate C. difficile colonization (CDC) from CDI ( Han et al, 2020 ).…”
Section: Clostridioides Difficile Infection and Dysbiosis In...mentioning
confidence: 99%
“…Alpha diversity at D7 (EPIFLORE_D7_2 dataset) was also higher when C. difficile was detected in samples from the same PN at D28. These findings are unusual compared to available data from 16S rRNA gene NGS analysis suggesting that C. difficile colonization is associated with a decreased alpha diversity of the gut microbiota in adults and children (Chen et al, 2019;Han et al, 2019;Crobach et al, 2020;Han et al, 2020). In a study performed in two Dutch NICUs, Crobach et al reported that the Shannon index was significantly higher in 43 control adult individuals than in 41 C. difficile-colonized or 41 -infected patients (p < 0.01), whereas no difference was seen between colonized and infected patients (Crobach et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…In a pediatric population (median age 14 years, range 4–19 years, n=113), alpha diversity was also significantly lower in the C. difficile -colonized group ( p = 0.029) ( Chen et al., 2019 ). However, another study showed no difference in alpha diversity (Chao1 index) between C. difficile -colonized (n=93) and control (n=93) adults ( p = 0.797) ( Han et al., 2020 ). Unlike older populations, our results suggest that in PN, C. difficile colonization is concomitant with physiological establishment and diversification of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations